2018
DOI: 10.1002/nop2.170
|View full text |Cite
|
Sign up to set email alerts
|

Concept analysis of impressionability among adolescents and young adults

Abstract: AimTo report a concept analysis of impressionability among adolescents and young adults.BackgroundAdolescence and young adulthood are critical periods to establish health behaviour. Environmental determinants are associated with youth health risk behaviours. These populations are impressionable to a range of social and physical environmental factors.DesignConcept analysis.MethodsWe selected 17 studies to review from Psych INFO, ERIC, MEDLINE, and Google Scholar as well as the University of Virginia library. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…Another potential explanation for the role of minority stressors in the younger age group is internalized transnegativity, which is internalized negative attitudes about transgender individuals and transgender identities. As young adults have been argued to be in a period where they are more impressionable to external stimuli than older adults (Gwon & Jeong, 2018; Krosnick & Alwin, 1989; Tyler & Schuller, 1991); this may also make them more vulnerable to internalize negative beliefs. For example, in transgender literature it has been reported that older transgender individuals have less internalized transnegativity than younger participants and that the relationship between age and psychological distress can be partially mediated by internalized transnegativity (Jackman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for the role of minority stressors in the younger age group is internalized transnegativity, which is internalized negative attitudes about transgender individuals and transgender identities. As young adults have been argued to be in a period where they are more impressionable to external stimuli than older adults (Gwon & Jeong, 2018; Krosnick & Alwin, 1989; Tyler & Schuller, 1991); this may also make them more vulnerable to internalize negative beliefs. For example, in transgender literature it has been reported that older transgender individuals have less internalized transnegativity than younger participants and that the relationship between age and psychological distress can be partially mediated by internalized transnegativity (Jackman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing persistence hypothesis proposes that people become gradually more resistant to change throughout their lives"; en (Krosnick & Alwin, 1989) se encuentra evidencia para la primera, pero lo cierto es que los paneles en los que se basa son muy limitados en recorrido temporal. El análisis conceptual de que se entiende por "impresionabilidad" está elaborado en (Gwon & Jeong, 2018). Los peligros de las comparaciones inter edad, con un interesante ejemplo práctico del impacto de priming del orden de las preguntas en un cuestionario en (Knauper, Schwarz, Park, & Fritsch, 2007).…”
Section: Discussionunclassified
“…The study quantitative ndings also show that older participants are more likely to practice protective sexual behaviours than younger ones, and this may be attributable to some reasons. Younger international students are likely to assimilate a new society's way of life because they are likely to be more impressionable than older ones 96,97 .…”
Section: Discussionmentioning
confidence: 99%